Local Peoples’ Participation in Natural Resources of Forest Tea and Environment Conservation Involved to Sustainable Tourism at Longpod Village, Phukhoun District, Luangprabang Province, Lao PDR - HERDERCHERSOUAVUE, Yengmouaxay; MANYSOAT , Soutthanou; BRIATIA, Xoxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aimed to study local peoples’ participation in natural resources of forest tea and environment conservation involved to sustainable tourism at Longpod Village, Phukhoun District, Luangprabang Province, Lao PDR. Population sample were 104 people with Yamane (1973) sample size formula and a cluster random sampling technique. The questionnaire was used to collect data. A percentage, a mean and standard deviation were employed to analyze data. Research results found that people mostly were female 61.54% (64 persons), aged 31 - 50 years, status married, education level primary and secondary school, being agriculture/farmer and monthly income was 500,000 – 2,000,000 Kips. Generally, people’s participation in natural resources of forest tea and environment conservation involved to sustainable tourism at Longpod Village, Phukhoun District, Luangprabang Province was at the high level such as in decision making ( , in operations ( , in receiving benefits ( and in evaluation ( . Considered, it can be seen that the local people agreed to participate in natural resources of forest tea and environment conservation involved to sustainable tourism in the future together with the public and private organizations at high level.